Business process management and service delivery; a case of Uganda’s public entities - Kamukama, Nixon; Tumwine, Sulait; Opiso, Julius; Korutaro Nkundabanyanga, Stephen (World Journal of Entrepreneurship, Management and Sustainable Development, 2014)
The purpose of this paper is to test empirically a variety of hypotheses related to business process management (BPM) and service delivery within public entities and contracting companies in Uganda. Design/methodology/approach – Avalid research instrument was utilized to conduct a survey on 20 government ministries, ten government departments and 13 service providers (contractors) who are representative of the 40 government entities and 25 service providers in Uganda. Correlation and regression analysis were conducted to ascertain the validity of the hypotheses. Findings – Statistical support was found for eight out of the nine hypotheses tested. Research limitations/implications – Only a single research methodological approach was employed, future research through interviews could be undertaken. Multiple respondents in public entities and service providers were studied, neglecting other key stakeholders like service users. Finally, BPM was studied and by the virtual of the results, there are other elements that contribute to service delivery that were not part of this study. Practical implications – There is need to intensify initiatives to encourage greater understanding and acceptance of BPM, employ a viable BPM strategy that includes risk management, building highlevel innovation, strong human resource capacity, providers expertise in order to provide optimal service to both service buyers and users. Originality/value – This is the first paper in sub-Saharan Africa to tests empirically the relationship between BPM and service delivery in the Ugandan context of service buyers and providers and provides support for the relationship and process management.
Keywords: Service delivery; Business process management; Service provider; Service buyer